Students’ Perspective on the Ethical Use of Artificial Intelligence in Academic Writing - Astuti, Widya; Nikmah, Siti Zumrotul (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The rapid development of technology like Artificial Intelligence (AI) has significantly influenced students’ approaches to academic writing. completing features such as grammar correction, vocabulary enhancement, and idea generation, their ethical implications remain contested. This study explores students’ perspectives on the ethical use of AI in academic writing. By using qualitative design, data were collected through interview and FGD toward 10 undergraduate students from Sharia tourism department in IAIN Takengon. After analyzing data using thematic analysis, The findings revealed nine key themes: (1) AI as a helpful support tool, (2) time efficiency and task completion, (3) enhancing creativity and expanding knowledge, (4) ease of task management, (5) concerns about academic integrity, (6) limited awareness of ethical guidelines, (7) the need for clear regulation and training, (8) dependence and overreliance risks, and (9) transparency and acknowledgment of AI use. These insights highlight both the potential benefits and ethical dilemmas students face when engaging with AI. The study contributes by recommending that policymakers establish clear regulations, provide systematic training, and promote transparency to ensure responsible and sustainable AI use in higher education.